Philosophical reflections in the framework of constants and concepts (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The essence of concepts is revealed in the article on the basis of concrete historical and logical-epistemological materials: “constant”, “concept”, “religion”, “religious belief”, “religious knowledge”. The epistemological meaning of conceptual and logical statements is considered, such as: religion is a “mirror” of a certain state of being; it can reflect people’s need to realize their place in the world; religious symbols and rituals can also reflect the state of being; religious traditions express the practices of spiritual development. The article scientifically substantiates and conceptually argues the claim that religion is often based on faith, revelation and spiritual experience, which cannot be empirically verified.
Keywords: constantа, concept, religion, symbol, fantastic reality; illusory reflection, practice, spiritual development, consciousness, myth, philosopheme, divine being, science, method, cognition